Pregnancy after surgical correction of tetralogy of Fallot. - Singh, H (1982)
Forty pregnancies have been documented in 27 patients with surgically corrected tetralogy of Fallot. Infertility was uncommon and there were no premature births and few abortions or small-for-dates babies; this suggests that surgery that corrects cyanosis improves the outcome of pregnancy by correcting the fetal environment. Pregnancy was well tolerated and there were no serious cardiac complications. Thirty of the 31 infants examined were normal, the one abnormal infant having pulmonary atresia. A patient with no major residual defects after surgery for tetralogy of Fallot may be reassured that pregnancy will be well tolerated and that delivery may be managed in the normal manner.